KEBIJAKAN LUAR NEGERI QATAR DALAM MENGATASI KRISIS TELUK DENGAN ARAB SAUDI TAHUN 2017-2019 - Divia Anjeli; Yusnarida Eka Nizmi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This research analyzes Qatar's foreign policy in overcoming its country's diplomatic crisis with Gulf countries, such as Saudi Arabia, United Arab Emirates (UAE), Bahrain, and Egypt. Qatar, as one of the small countries in the Middle East region, can rise; this is, of course, supported by bold foreign policy making and trying not to be bound by the foreign policy of the Saudi Arabian government. However, the bold step taken by Qatar to become a country with a foreign policy based on open-door diplomacy is vehemently opposed by other Gulf states. So to minimize Qatar's influence in the Gulf region, Saudi Arabia, together with the anti-Qatar quartet, imposed diplomatic sanctions on Qatar by severing diplomatic relations and closing all air, sea, and land routes from and to Qatar. This study aims to determine the trigger for the termination of diplomatic relations between Qatar and the anti-Qatar quartet so that the blockade is enforced and how to implement an open-door diplomacy foreign policy. This research uses a qualitative research method, with a literature study using secondary data sources obtained through books, journals, articles, the internet, and documents related to this research. This study uses the theory of Foreign Policy. This research shows that the decision taken by the Qatari leader to change its foreign policy led to disapproval from countries in the Middle East, thus bringing the relations of the Gulf countries towards disharmony and causing a diplomatic crisis. However, as a sovereign state, Qatar has the right to determine the foundation and principles of its government's foreign policy. As well as restoring relations between Qatar and the anti-Qatar quartet, both sides agreed to end the crisis through diplomatic dialogues and negotiations, lifting the sanctions blockade on Qatar. Keywords: Foreign Policy, Diplomacy, Blockade, Independent, Open Door Policy.